Public vision, private lives Rousseau, religion, and 21st-century democracy - Cladis, Mark Sydney; Oxford eBooks (Oxford : Oxford University Press, 2003)
This text invites us to reflect on the nature and place of public and private in the work of Rousseau and, more generally in society. It explores the conflicts with which Rousseau wrestled - prerogatives and obligations to self, friends family, civic life, and to humanity.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Rousseau, Jean-Jacques, -- 1712-1778.; Democracy; Privacy; Public interest; Religion and politics; Electronic books